2007
DOI: 10.1093/hmg/ddm185
|View full text |Cite
|
Sign up to set email alerts
|

Cell-specific expression of wild-type MeCP2 in mouse models of Rett syndrome yields insight about pathogenesis

Abstract: Rett syndrome (RTT), a leading cause of mental retardation with autistic features in females, is caused by mutations in the gene encoding methyl-CpG-binding protein 2 (MeCP2). RTT is characterized by a diverse set of neurological features that includes cognitive, motor, behavioral and autonomic disturbances. The diverse features suggest that specific neurons contribute to particular phenotypes and raise the question whether restoring MeCP2 function in a cell-specific manner will rescue some of the phenotypes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 36 publications
2
50
1
Order By: Relevance
“…We have previously reported that transgenic mice expressing MeCP2-e2 under the NSE or CamKIIa promoters, when crossed to Mecp2 À/y elicited no significant behavioral or lifespan improvements. 27 Contrasting this previous study with the current data, in which we observe significant phenotypic prevention with widespread brain expression of MeCP2-e2, suggests that not only level, but also location of expression is important for MeCP2's overall activity in brain function. In addition, the expression of transgenic MeCP2 in glial cells in the transgenic mice described in this report could contribute to the behavioral amelioration and might explain the different results observed.…”
Section: Discussioncontrasting
confidence: 99%
“…We have previously reported that transgenic mice expressing MeCP2-e2 under the NSE or CamKIIa promoters, when crossed to Mecp2 À/y elicited no significant behavioral or lifespan improvements. 27 Contrasting this previous study with the current data, in which we observe significant phenotypic prevention with widespread brain expression of MeCP2-e2, suggests that not only level, but also location of expression is important for MeCP2's overall activity in brain function. In addition, the expression of transgenic MeCP2 in glial cells in the transgenic mice described in this report could contribute to the behavioral amelioration and might explain the different results observed.…”
Section: Discussioncontrasting
confidence: 99%
“…White matter regions were generally void of labeling, while the cerebral cortical layers and a number of subcortical regions demonstrated quite a substantial level of labeling. In accordance with previous reports (Bukalo et al, 2004;Chen et al, 1998;Mayford et al, 1996;Michalon et al, 2005;Alvarez-Saavedra et al, 2007), our examination of location and morphological characteristics of labeled cells gives the distinct impression that X-gal labeling is confined primarily to neurons (Fig. 4), with no association to glia.…”
Section: Distribution Of Camkii Promoter Activity In the Brainsupporting
confidence: 92%
“…The PrP promoter line has been successfully used in several studies of various diseases, including prion diseases (Safar et al, 2005;Tremblay et al, 1998), Parkinson's disease (Nuber et al, 2008), analysis of alcohol consumption (Choi et al, 2002), spinocerebellar ataxia type 3 (Boy et al, 2009), and neurofilament transport (Millecamps et al, 2007). The CamKII promoter line has been used for the investigation of synaptic plasticity, learning and memory consolidation (Bukalo et al, 2004;Limback-Stokin et al, 2004;Mayford et al, 1997;Wood et al, 2005), neurodevelopmental disorders (Alvarez-Saavedra et al, 2007;Jerecic et al, 2001), and for the generation of transgenic mouse models for Alzheimer's disease (Jankowsky et al, 2005), Huntington's disease (Yamamoto et al, 2000), Parkinson's disease (Nuber et al, 2008), neocortical degeneration (Muyllaert et al, 2008), schizophrenia (Pletnikov et al, 2008), and neurofibromatosis (Saito et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One such example is Rett syndrome, which is a rare neurodevelopmental disease caused by loss-of-function mutations in the X-linked gene MECP2 encoding Methyl CpG binding protein. As discussed above, reactivating Xi-linked MECP2 in Rett syndrome patients can restore symptoms associated with the disease and possibly reverse the disease [74][75][76] . But the lack of understanding of XCI has limited its applicability as a target for treatment.…”
Section: Final Remarksmentioning
confidence: 97%